2020
DOI: 10.1371/journal.pgen.1008787
|View full text |Cite
|
Sign up to set email alerts
|

ALC1/eIF4A1-mediated regulation of CtIP mRNA stability controls DNA end resection

Abstract: During repair of DNA double-strand breaks, resection of DNA ends influences how these lesions will be repaired. If resection is activated, the break will be channeled through homologous recombination; if not, it will be simply ligated using the non-homologous end-joining machinery. Regulation of resection relies greatly on modulating CtIP, which can be done by modifying: i) its interaction partners, ii) its post-translational modifications, or iii) its cellular levels, by regulating transcription, splicing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Mostly, translational initiation factor family were ‘house-keeping genes’ and initiation of translation is the rate-limiting step in protein synthesis in all living cells ( Mejias-Navarro et al, 2020 ). These factors have been proven to play a vital role in wound healing, tumorigenesis, cell stemness and epithelial-mesenchymal transition, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, translational initiation factor family were ‘house-keeping genes’ and initiation of translation is the rate-limiting step in protein synthesis in all living cells ( Mejias-Navarro et al, 2020 ). These factors have been proven to play a vital role in wound healing, tumorigenesis, cell stemness and epithelial-mesenchymal transition, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the frequent chromosomal changes, the parrot genomes have a slightly higher proportion of transposable elements than other birds due to recent CR1 proliferation, and we speculate that recent CR1-psi accumulation may have provided substrates for ectopic recombination events leading to chromosomal rearrangements and the loss of at least some of the 72 conserved genes. Among the lost genes, ALC1 and PARP3 are known for their roles in genome stability and DNA double strand repair (Ahel et al 2009;Day et al 2017;Mejías-Navarro et al 2020;Boehler et al 2011;Beck et al 2014Beck et al , 2019Sellou et al 2016;Tsuda et al 2017;Zarkovic et al 2018;Belousova et al 2018;Grundy et al 2016). It has been demonstrated that deletion of ALC1 impacts chromatin relaxation which is a crucial step in responses to DNA damage (Sellou et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…and PARP3, are related to repair of DNA damage and maintenance of genome stability (Ahel et al 2009;Day et al 2017;Mejías-Navarro et al 2020;Boehler et al 2011;Beck et al 2014Beck et al , 2019Sellou et al 2016;Tsuda et al 2017;Belousova et al 2018;Zarkovic et al 2018;Grundy et al 2016). Among the 72 lost genes, 24 reside in conserved synteny blocks (collinear gene order) across bird species (Fig.…”
Section: Parrot-specific Gene Lossmentioning
confidence: 99%
“…As described previously [24], protein extracts were prepared in 2× Laemmli buffer (4% SDS, 20% glycerol, 125 m m Tris/HCl, pH 6.8) and passed 10 times through a 0.5‐mm needle‐mounted syringe to reduce viscosity. Proteins were resolved by SDS/PAGE and transferred to low fluorescence PVDF membranes (Immobilon‐FL; Millipore, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We used the same protocol previously described in [24]. Briefly, cells were fixed with cold 70% ethanol overnight, incubated with 250 μg·mL −1 RNase A (Sigma) and 10 μg·mL −1 propidium iodide (Fluka, Buchs, Switzerland) at 37 ºC for 30 min, and analyzed with a FACSCalibur (BD, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%